Pendampingan Pembuatan Rengginang dalam Mendukung Diversifikasi Pengolahan Wortel di Desa Sembalun Kecamatan Sembalun Kabupaten Lombok Timur - Madani, Nia Ulfa; Yuliatin Hasfiani; Rahayu Safitri Rahman (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
This community service program aims to enhance the capacity of the Sembalun Village community, Sembalun District, East Lombok Regency, to process carrots into value-added food products, specifically carrot rengginang, through practice-based training and mentoring. The activity is carried out through several stages, including preparation, socialization, training, mentoring, and strengthening aspects of product branding and promotion. The preparation stage includes coordination with the village government, identifying community needs, and providing tools, materials, and training materials. The activity continues with the delivery of material on the potential for diversification of carrot processing, product benefits, and opportunities for its development as a community business. The training is carried out through demonstrations and direct practice of making carrot rengginang starting from raw material preparation, processing, to product packaging. The mentoring activities also cover business management, determining selling prices, and developing promotional media through digital platforms. The results of the activity show an increase in community knowledge and skills in processing carrots into innovative food products with higher economic value. This program is expected to support local food diversification, reduce carrot crop losses, increase the added value of agricultural commodities, and strengthen the economy of the Sembalun Village community through the development of local food-based businesses.